2021
DOI: 10.1002/nop2.1049
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative efficacy of non‐pharmacological interventions on behavioural and psychological symptoms in elders with dementia: A network meta‐analysis

Abstract: Dementia is a progressive neurodegenerative syndrome manifested by cognitive impairment, memory loss as well as behavioural and psychological disorders, which has posed a great burden on both human health and global economy. The global rising of life expectancy and an increasing proportion of elders in the population are the main reasons for worldwide population ageing (Heese, 2015).According to the World Alzheimer Report 2018, dementia affects about 50 million people and this number is expected to increase to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Compared with pharmacological interventions, nonpharmacological interventions are low-cost, low-risk, and simple to perform, which have been widely used for various diseases. [ 11 14 ]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with pharmacological interventions, nonpharmacological interventions are low-cost, low-risk, and simple to perform, which have been widely used for various diseases. [ 11 14 ]…”
Section: Introductionmentioning
confidence: 99%
“…Compared with pharmacological interventions, nonpharmacological interventions are low-cost, low-risk, and simple to perform, which have been widely used for various diseases. [11][12][13][14] Although many randomized controlled trials (RCTs) have reported the effects of nonpharmacologic interventions on alleviating pain and improving sleep quality after percutaneous nephrolithotomy, their results may be inconsistent or even contradictory. [5,[15][16][17] In addition, evidence for comparing the effectiveness of these strategies is scant, which may affect the clinical application and scientific reliability of the results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As drug treatment for dementia has limitations such as medical contraindications, limited efficacy, and adverse effects (Azhar et al, 2022;Wong, 2016), non-pharmacological therapy has been increasingly regarded as a critical part of comprehensive dementia care (Li et al, 2021;Sink et al, 2005). Phototherapy, which utilizes full-spectrum bright light usually above 600 lux (Onega et al, 2016;Zou et al, 2022) or wavelength-specific lights, such as blue-enriched (Cremascoli et al, 2021) or blue-green (Nowak, 2008) lights, is a promising nonpharmacological therapy that has the advantages of non-invasiveness, inexpensive, and high safety (Forbes et al, 2014;C.-R. Liu et al, 2021;Scales et al, 2018).…”
mentioning
confidence: 99%
“…In Li et al. ( 2021 ), the authors have noticed errors in the affiliations of the following authors. The correct affiliations are provided below.…”
mentioning
confidence: 99%